Pengaruh Pertumbuhan Penjualan, Ukuran Perusahaan, Leverage, Profitabilitas, Likuiditas, Kualitas Audit, dan Ketepatan Waktu Laporan Keuangan terhadap Nilai Perusahaan Sektor Teknologi yang Terdaftar di Bursa Efek Indonesia - Wulandari, Resti; Sihono, Agus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
Firm value is an important indicator reflecting investor perceptions of a company's performance and future prospects and is often used to assess shareholder welfare. This study aims to analyze the influence of sales growth, firm size, leverage, profitability, liquidity, audit quality, and timeliness of financial reports on firm value in the technology sector in Indonesia. The data used includes 135 financial reports from 27 technology companies listed on the Indonesia Stock Exchange during the 2020-2024 period. The analytical approach used was multiple linear regression with classical assumption testing and hypothesis testing. The results show that sales growth, firm size, and profitability have a significant effect on firm value. Conversely, leverage, liquidity, audit quality, and timeliness of financial reports do not show a significant effect. The implications of this study's results suggest that technology company management needs to pay more attention to sales growth strategies and asset efficiency to create greater value for investors. Furthermore, investors and market analysts should prioritize fundamental aspects such as growth and profitability rather than relying solely on administrative compliance or capital structure in assessing a company's investment viability.